2010
DOI: 10.1074/jbc.m110.142356
|View full text |Cite
|
Sign up to set email alerts
|

Galantamine-induced Amyloid-β Clearance Mediated via Stimulation of Microglial Nicotinic Acetylcholine Receptors

Abstract: Reduction of brain amyloid-␤ (A␤) has been proposed as a therapeutic target for Alzheimer disease (AD), and microglial A␤ phagocytosis is noted as an A␤ clearance system in brains. Galantamine is an acetylcholinesterase inhibitor approved for symptomatic treatment of AD. Galantamine also acts as an allosterically potentiating ligand (APL) for nicotinic acetylcholine receptors (nAChRs). APL-binding site is located close to but distinct from that for acetylcholine on nAChRs, and FK1 antibody specifically binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 55 publications
0
101
0
1
Order By: Relevance
“…In the second study, elevated plasma sAPPα was found in 60% of known autistic children (n = 25) compared to healthy age-matched controls (Bailey et al, 2008). Recent studies showed that galantamine allosterically modulates microglial nAChRs and increases microglial beta-amyloid (A) phagocytosis Takata et al, 2010). Collectively, these studies suggest that positive allosteric modulators of 42 nAChRs, when used by themselves or in conjunction with agonists, may be beneficial in correcting deficits in the functions of 42 nAChRs and thereby core deficits of ASD.…”
Section: Positive Allosteric Modulatorsmentioning
confidence: 95%
“…In the second study, elevated plasma sAPPα was found in 60% of known autistic children (n = 25) compared to healthy age-matched controls (Bailey et al, 2008). Recent studies showed that galantamine allosterically modulates microglial nAChRs and increases microglial beta-amyloid (A) phagocytosis Takata et al, 2010). Collectively, these studies suggest that positive allosteric modulators of 42 nAChRs, when used by themselves or in conjunction with agonists, may be beneficial in correcting deficits in the functions of 42 nAChRs and thereby core deficits of ASD.…”
Section: Positive Allosteric Modulatorsmentioning
confidence: 95%
“…We have recently provided new evidence that modulation of microglial α7 nicotinic acetylcholine receptors (nAChRs) by galantamine or stimulation of α7 nAChRs by nicotine enhances Aβ phagocytosis in primary cultured rat microglia (51). Galantamine sensitizes microglial α7 nAChRs to choline and nicotine by binding to the allosterically potentiating ligand-binding site on α7 nAChRs.…”
Section: Microglial Accumulation On Aβ Depositions In Ad Brainsmentioning
confidence: 99%
“…In this amyloidosis microglia could exert neuroprotective activity by degrading Aβ (55). In AD, these cells have a reduced capacity for Aβ clearance, which results in additional accumulation of this peptide (56).…”
Section: Role Of Aβ In Brain Inflammationmentioning
confidence: 99%